EFFICIENT TRANSFER OF KNOWLEDGE IN AGRICULTURE THROUGH COOPERATIVE STRUCTURES - Popescu, Gabriel; Constantin, Florentina; Menda, Teodora (Economics of Agriculture, 2018)
In broad, deep and dynamic process of knowledge transfer, the cooperative structures can have a decided role in improving the information as a factor of production in agriculture. The process of defining a cooperative structure, as the intermediate link between producers and consumers of information and taking in consideration the principles of economic liberalism requires going through several steps which well-define, in the implementation of projects with European funding philosophy, can become self-standing actions. In this context, it is important to establish criteria through which are defined the target group, tools for promoting the new, and patterns for managing market relationships of agricultural markets.